2022
DOI: 10.1177/00031348221101475
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Trauma During the COVID Pandemic: Just Like Adults, Children, or Someone Else?

Abstract: COVID-19 stay-at-home (SAH) orders were impactful on adolescence, when social interactions affect development. This has the potential to change adolescent trauma. A post-hoc multicenter retrospective analysis of adolescent (13-17 years-old) trauma patients (ATPs) at 11 trauma centers was performed. Patients were divided into 3 groups based on injury date: historical control (CONTROL:3/19/2019-6/30/2019, before SAH (PRE:1/1/2020-3/18/2020), and after SAH (POST:3/19/2020-6/30/2020). The POST group was compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 18 publications
1
13
1
Order By: Relevance
“…There were few significant differences in volume of violent injuries reported by authors in the first few months of the COVID-19 pandemic compared to historical controls [ 15 , 16 , 17 , 18 , 19 ]. Sanford et al noted that intentional blunt injuries (defined by assaults, NAT, and self-harm injuries in the study) decreased at the start of the COVID-19 era (pre-pandemic mean 20.6 children [95% confidence interval (CI) 16.1-25.1] vs. post-pandemic mean 17 children, p=0.04) [ 20 ].…”
Section: Classifications Of Violent Injurymentioning
confidence: 86%
“…There were few significant differences in volume of violent injuries reported by authors in the first few months of the COVID-19 pandemic compared to historical controls [ 15 , 16 , 17 , 18 , 19 ]. Sanford et al noted that intentional blunt injuries (defined by assaults, NAT, and self-harm injuries in the study) decreased at the start of the COVID-19 era (pre-pandemic mean 20.6 children [95% confidence interval (CI) 16.1-25.1] vs. post-pandemic mean 17 children, p=0.04) [ 20 ].…”
Section: Classifications Of Violent Injurymentioning
confidence: 86%
“…Some early pandemic studies revealed a spike in firearm injuries, 2,3 whereas others found unchanged rates. 4,5 We evaluated contemporary trends in pediatric firearm injuries before and during the pandemic to determine whether sociodemographic risk factors were similar.…”
Section: Surge In Pediatric Firearm Injuries Presenting To Us Childre...mentioning
confidence: 99%
“…Some early pandemic studies revealed a spike in firearm injuries, 2,3 whereas others found unchanged rates. 4,5 We evaluated contemporary trends in pediatric firearm injuries before and during the pandemic to determine whether sociodemographic risk factors were similar.Methods | This retrospective cohort study used data from the Pediatric Health Information System (PHIS), an administra-Table. Characteristics of Children With Firearm Injuries Before vs After the COVID-19 Pandemic Characteristic Children, No.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest a report published by Ruhi-Williams et al 1 in which a study was conducted to determine adolescent trauma during the COVID-19 pandemic compared to adults and children in the state of California. Ruhi-Williams and the authors provide great insight into the implications of the pandemic between 2019 and 2020 on adolescents, such as higher drug positivity and suicide attempts.…”
mentioning
confidence: 99%